Exploring Students' Cognitive Engagement in English Language Classrooms Through Mobile-Assisted Language Learning (MALL) - Qorry Annisa; Maisa; Devi Mulatsih (Journal of Educational Management Research, 2026)
This study aimed to explore students' cognitive engagement during the learning of Passive Voice through Educaplay's Froggy Jump feature within a Mobile-Assisted Language Learning (MALL) environment. A qualitative case study design was employed involving five Grade XI students and one English teacher at a senior high school in Cirebon, Indonesia. Data were collected through semi-structured interviews, classroom observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings revealed four interconnected dimensions of cognitive engagement: deep learning strategies, self-regulation, mental effort and persistence, and strategic problem solving. Students actively analyzed grammatical structures, monitored their understanding, sustained cognitive effort despite learning difficulties, and developed strategies to solve Passive Voice tasks collaboratively. The study concludes that gamified MALL fosters meaningful cognitive engagement when supported by teacher scaffolding and peer interaction. These findings imply that English teachers should integrate gamified mobile learning with reflective and collaborative instructional practices to promote deeper grammar learning and higher-order thinking.